Green national accounting for welfare and sustainability: A taxonomy of assumptions and results - Geir B. Asheim (University of Oslo, Department of Economics, 2002)
This paper summarizes assumptions made and results obtained in parts of the literature on welfare and sustainability accounting. I consider five di®erent assumptions that can be imposed independently of each other, producing 32 different combinations. This taxonomy is used to organize results in welfare and sustainability accounting. The analysis illustrates how stronger results require stronger assumptions and thereby impose harder informational requirements.
Keywords: C43; O47; Q01; 330; National accounting; dynamic welfare; sustainability; Ökosozialprodukt; Soziale Wohlfahrtsfunktion; Nachhaltige Entwicklung; Theorie